Readability Analysis of Local Wisdom Non-Fiction Texts in Android-Based Interactive Multimedia for Elementary School Students With Fry Graph Formulas - Mahendri, Ravinda; Mujiwati, Endang Sri; Aka, Kukuh Andri (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2022)
The purpose of this study was to analyze the legibility of non-fiction texts containing Kediri Raya local wisdom in Android-based interactive multimedia intended for 4th grade elementary school students with the readability formula of the Fry Graph. The method in this research is descriptive quantitative. The objects of this research are ten non-fiction texts containing local wisdom in Kediri Raya. The research instrument uses documentation with data collected in the form of non-fiction texts of local wisdom of Kediri Raya in Android-based interactive multimedia. Analysis of the data in this study using the Fry Graph formula as a guide for analyzing the level of readability in non-fiction texts. The results showed that the readability level of ten non-fiction texts containing Kediri Raya local wisdom in Android-based interactive multimedia had the feasibility and suitability of the readability level for 4th grade elementary school students, because the readability levels of these ten nonfiction texts were in areas 2, 3, 4 and 6 which means the non-fiction text of Kediri Raya’s local wisdom in interactive multimedia based on Android is suitable and appropriate for grades 2, 3, 4 and 6 of elementary school.